Outcomes for Children With Type II and Type III Pleuropulmonary Blastoma Following Chemotherapy: A Report From the International PPB/DICER1 Registry. Issue 4 (1st February 2023) - Schultz, Kris Ann P.; Harris, Anne K.; Nelson, Alexander T.; Watson, Dave; Lucas, John T.; Miniati, Doug; Stewart, Douglas R.; Hagedorn, Kelly N.; Mize, William; Kamihara, Junne; Mitchell, Sarah G.; Wilson, David B.; et al.
Abstract : PURPOSE: Pleuropulmonary blastoma (PPB) is the most common primary lung neoplasm of infancy and early childhood. Type II and type III PPB have historically been associated with a poor prognosis. METHODS: Patients with known or suspected PPB were enrolled in the International PPB/ DICER1 Registry. Medical records were abstracted with follow-up ascertained annually. All PPB diagnoses were confirmed by central pathology review. Beginning in 2007, the IVADo regimen (ifosfamide, vincristine, actinomycin-D, and doxorubicin) was recommended as a potential treatment regimen for children with type II and type III PPB. This regimen was compared with a historical control cohort. RESULTS: From 1987 to 2021, 314 children with centrally confirmed type II and type III PPB who received upfront chemotherapy were enrolled; 132 children (75 with type II and 57 with type III) received IVADo chemotherapy. Adjusted analyses suggest improved overall survival for children treated with IVADo in comparison with historical controls with an estimated hazard ratio of 0.65 (95% CI, 0.39 to 1.08). Compared with localized disease, distant metastasis at diagnosis was associated with worse PPB event-free survival and overall survival with hazard ratio of 4.23 (95% CI, 2.42 to 7.38) and 4.69 (95% CI, 2.50 to 8.80), respectively. CONCLUSION: The use of IVADo in children with type II and type III PPB resulted in similar-to-improved outcomes compared with historical controls. Inferior outcomes with metastatic disease suggest the need for novel therapies. This large cohort of uniformly treated children with advanced PPB serves as a benchmark for future multicenter therapeutic studies for this rare pediatric tumor.